MoodP, AspP and TP in the Jaminawa language (Kayapucá variant): a review considering recent theories in the field of Syntax - Shelton Lima de Souza (Revista Linguística, 2022)
This paper discusses the viability of the proposal of a Mood projection to project the tense and aspect categories in Jaminawa, according to the hypothesis of Soares (2006), which proposes a Mood phrase for the Panoan languages. In the Jaminawa language, our hypothesis is that speakers distinguish verbal events only as those which happened (and the truth of the fact can be proven), and those which have not (hence the truth can not be certified). That is, this language would represent the mood category with the feature [+realis]. This way, we could relate Mood with the [+ realis] feature of the language to the past tense (having the present- now- as the basis), and relate it with the [-realis] feature to the non-past tense (events that have not occurred, are ongoing, or will still happen), which allows us to consider Soares’ proposal (2006), regarding the possibility of thinking about a functional projection Mood (MoodP) as relevant for the Jaminawa language. In addition, we verify that there is a dissociation between the features that make up the TAM morphemes, leading us to suggest a dissociation between the functional heads Asp and T, both projecting the phrases AspP and TP, the first being higher than the second in the syntagma hierarchy of the language under analysis.